Pengaruh Creative Marketing Dan User Generated Content Di Platform Roblox Terhadap Brand Awareness Pada Generasi Z - Syarla Martiza Arian Putri; Yuli Ardianto (Universitas Pakuan, 2026)
THE INFLUENCE OF CREATIVE MARKETING AND USER-GENERATED CONTENT (UGC) ON THE ROBLOX PLATFORM ON BRAND AWARENESS AMONG GENERATION Z This study is motivated by the shift in media consumption preferences among Generation Z, who tend to resist conventional advertising (hard selling) on two-dimensional platforms, thereby creating a trust gap. As a solution, global brands have begun to leverage immersive metaverse platforms. This study aims to analyze the partial and simultaneous effects of implementing Creative Marketing and User Generated Content (UGC) on the Roblox platform toward building Brand Awareness among Generation Z. The method used in this research is quantitative with a causal associative approach. Primary data were collected through online questionnaires using a purposive sampling technique involving 100 respondents who are active Roblox users aged 12 to 27 years old. The data analysis techniques applied include classical assumption tests, multiple linear regression analysis, coefficient of determination (), and hypothesis testing through t-tests and F-tests assisted by SPSS software. The hypothesis testing results show that partially, the Creative Marketing variable has a positive and significant effect on Brand Awareness. The User Generated Content variable is also proven to have a positive and significant partial effect on Brand Awareness. Furthermore, simultaneous testing demonstrates that both independent variables together have a significant effect on the formation of brand awareness. The conclusion of this study confirms that the integration between interactive creative strategies from companies and the active involvement of the community in producing virtual content is proven effective in building strong brand recall among Generation Z within the metaverse.